Conflict Management The Jakmania Orange Gardens In Managing Problems Organization - Alfirahmi, Alfirahmi; Pratama, Harindra Alrizki (Jurnal Ilmu Sosial Mamangan, 2025)
Conflicts within the club's supporter groups football can be caused by internal factors and external. Internal factors related to problems that occur in the body organization, both in terms of management and members of the organization. The conflict occurs due to ineffective communication between group members, so that resulting in misunderstanding, misunderstanding, or even more conflict great. Therefore, the purpose of this study is to determine and analyze conflict management Football Club Persija (the Jakmania) obstacles faced and and the solution given. The method used in this study is the study the case with qualitative types of research. The results of this study show that 1) Conflict management is done by means of) competition (competing), seen in the attitude the Jakmania competition in the form of differences of opinion that tend to compete, B) compromise (compromising), which is a form of compromise found in conflict management the Jakmania is adapting to differences of opinion to reach an agreement together, talk openly, and do meeting of all members of the Jakmani. 2) the obstacles faced are communication bad because of limited communication or lack of effort to each other listen, and understand the views of others. Difficulty finding a solution together, because of deep differences and stubborn attitudes. 3) solution what is done is to improve communication, and create an environment that allows all members to communicate openly and effectively, and support discussion and appreciate the views different. Keywords: conflict management, internal communication, external communication.